1994
DOI: 10.1002/aic.690400516
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fed‐batch control of induced foreign protein production by recombinant bacteria

Abstract: Optimal control strategies for maximizing the production of induced foreign protein by recombinant bacteria were sought by the optimal control theory. Nutrient and inducer feeding rates were selected as key control variables. Since the problem is linear in the control variables, the optimal control is bang-bang or singular. Singular solutions are shown to exist. The optimal control theory showed that the specific growth rate with respect to nutrient concentration must be kept in its maximum phase and that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 10 publications
(12 reference statements)
0
74
2
3
Order By: Relevance
“…The second case study involves induced foreign protein production by recombinant bacteria, 325 firstly proposed by Lee and Ramirez (1994). The problem was later modified by Tholudur and 326 Ramirez ( (17) 333 The PI is defined as: 339…”
Section: Case Study 324mentioning
confidence: 99%
“…The second case study involves induced foreign protein production by recombinant bacteria, 325 firstly proposed by Lee and Ramirez (1994). The problem was later modified by Tholudur and 326 Ramirez ( (17) 333 The PI is defined as: 339…”
Section: Case Study 324mentioning
confidence: 99%
“…The optimal control policy for maximization of secreted protein in a fed-batch reactor was found to consist of multiple singular arcs and an iterative strategy was developed to ®nd the optimal transitions between such arcs on the basis of minimum principle of Pontryagin [62]. Lee and Ramirez [63] derived singular control solutions for maximizing production of induced foreign protein by recombinant bacteria using nutrient and inducer feeding rates as control variables and compared the performance with bang-bang control solution and concluded that for the example considered, best bang-bang control is nearly equivalent to the optimal singular control.…”
Section: Singular Control Approachesmentioning
confidence: 99%
“…The main disadvantage of this method is that the algorithm may converge to local minima in many cases [3]. In addition, Lee and Ramirez [5] found an analytical solution for industrial foreign protein production by recombinant bacteria. Their problem had two control variables, and the algorithm was difficult to implement.…”
Section: Introductionmentioning
confidence: 99%